2015
DOI: 10.1086/681252
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization affects food webs and leaf-litter decomposition in a tropical stream in Malaysia

Abstract: Urbanization is occurring rapidly in southeastern Asia where streams are increasingly pressured. We assessed the ecological integrity of Ampang River in Kuala Lumpur by comparing structural and functional measures between forested and urban sites. We assessed 4 forested, 1 intermediate (deforested, not channelized), and 5 urban, channelized sites. Urbanization altered substrate (concrete at urban sites), riparian vegetation, light, temperature, O 2 , conductivity, nutrients, and major ion levels, and simplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…Yule et al. () suggested that urban development simplifies stream food webs, primarily by reducing richness, and decreasing abundances of some trophic guilds (e.g., shredders and predators). However, we do not know how the proliferation of synanthropes omnivores affects the stability and resilience of urban food webs, or how the availability of anthropogenic resources affects niche width.…”
Section: The Urban Food Web As a Wholementioning
confidence: 99%
See 2 more Smart Citations
“…Yule et al. () suggested that urban development simplifies stream food webs, primarily by reducing richness, and decreasing abundances of some trophic guilds (e.g., shredders and predators). However, we do not know how the proliferation of synanthropes omnivores affects the stability and resilience of urban food webs, or how the availability of anthropogenic resources affects niche width.…”
Section: The Urban Food Web As a Wholementioning
confidence: 99%
“…It also affects how allochthonous subsidies are processed. Urbanization alters leaf decay, an important ecosystem process in stream ecosystems, through changes in riparian plant composition, hydrology, shredding insects, microbial diversity or nutrient concentration (Cook & Hoellein, 2016;Yule, Gan, Jinggut, & Lee, 2015). Human waste (sewage and garbage) might also directly subsidize aquatic organisms (Singer & Battin, 2007).…”
Section: Anthropogenic Subsidies (Allochthonous Resources)mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative importance of temperature and litter quality is explored across elevation gradients by Jinggut and Yule (2015). Martins et al (2015) and Yule et al (2015) use leaf-litter breakdown as a tool to understand how urbanization affects ecosystem function of tropical streams. Last, Boyero et al (2015) present the results of a pantropical study that highlights the large amount of variability in this process within and among tropical regions.…”
Section: Aquatic Fauna and The Processing Of Organic Mattermentioning
confidence: 99%
“…Furthermore, benthic macroinvertebrates can also be used to monitor environmental deterioration. Taxa composition, abundance, diet, and many other characteristics of the macroinvertebrate community can be affected by anthropogenic disturbances (Yule, Boyero, & Marchant, ; Yule, Gan, Jinggut, & Lee, ). Macroinvertebrates have been used in water biomonitoring due to their high biodiversity, simplicity of sampling, and relatively longer life cycles than those of periphyton, fungi, and bacteria, which enables macroinvertebrates to reflect long‐term stress (Al‐Shami, Rawi, Ahmad, Hamid, & Nor, ; Hofmann, Hürdler, Ibisch, Schaeffer, & Borchardt, ; Morse et al, ).…”
Section: Introductionmentioning
confidence: 99%